Metabolic profiling of potential probiotic or synbiotic cheeses by nuclear magnetic resonance (NMR) spectroscopy - Rodrigues, Dina (2019)
To assess ripening of potential probiotic cheeses (containing either Lactobacillus casei-01 or Bifidobacterium lactis B94) or synbiotic cheeses with fructooligosaccharides (FOS) or a 50:50 mix of FOS/inulin, metabolic profiles have been obtained via classical biochemical analyses and by NMR spectroscopy. The addition of prebiotics to the cheeses resulted in lower proteolysis indices, especially in those synbiotic cheeses inoculated with B. lactis B94. Among synbiotic cheeses the combination of FOS and inulin resulted in an increase in lipolytic activity. The metabolic profiles of the cheeses analyzed by NMR spectroscopy, combined with multivariate statistics, allowed profiles to be distinguished by maturation time, added probiotic bacteria, or, in the case of B. lactis B94 cheese, added prebiotic. The NMR results are in agreement with the biochemical analyses and demonstrate the potential of NMR for the study of metabolic processes in probiotic/synbiotic food matrices.